Income analysis of cabbage farming in Kopeng village, Getasan district, Semarang regency: An effort to improve village community economies - Saputro, Wahyu Ardian (Journal of Sustainability, Society, and Eco-Welfare, 2024)
This study aims to analyze the Business Income of Cabbage Farming in Kopeng Village, Getasan District, Semarang Regency. The basic method in this study uses descriptive quantitative data collection techniques using questionnaires, interviews and observations. The sample in this study were Cabbage Farmers in Kopeng Village, Getasan District, Semarang Regency. Based on the results of the T test using the one sample test, the results of the T count were 24.407. Then it can be obtained that T count > T table, meaning that if T hcount > T table then HO is rejected, HA is accepted. So the hypothesis in this study can be concluded that cabbage farming in Kopeng Village, Getasan District, Semarang Regency is profitable.